2014
DOI: 10.5152/tjbh.2014.1602
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Breast Abscess Caused by E.coli in a Non-lactating Woman: A Rare Case

Abstract: Breast abscess usually occurs during lactation and the responsible organism is often S.Aureus. Breast abscess in non-lactating women is extremely rare and limited data is available in the literature regarding this entity. In our study, a 36-year-old non-lactating female patient who developed bilateral breast abscess due to E.coli infection without any predisposing factors has been discussed in light of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…A literature review showed there was a case published by Simsek [ 6 ] that discussed a 36-year-old female who developed an E. coli breast abscess bilaterally. This was managed with surgical incision and drainage, and adequate antibiotics cover post drainage.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review showed there was a case published by Simsek [ 6 ] that discussed a 36-year-old female who developed an E. coli breast abscess bilaterally. This was managed with surgical incision and drainage, and adequate antibiotics cover post drainage.…”
Section: Discussionmentioning
confidence: 99%